2004
DOI: 10.1038/sj.bjc.6601891
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with epirubicin, docetaxel and cisplatin (EDP) in metastatic or recurrent, unresectable gastric cancer

Abstract: Based on single agent activities and the additive or synergistic effects of three individual drugs in gastric cancer, we performed a phase II study of a new regimen combining epirubicin, docetaxel and cisplatin (EDP) for unresectable gastric cancer. The patients with histologically confirmed metastatic or recurrent, unresectable gastric cancer and no history of palliative chemotherapy were eligible for this trial. In total, 40 mg m À2 epirubicin (reduced to 30 mg m À2 due to high incidence of febrile neutropae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…By comparison, there was a nonsignificant trend for increased median survival with ILF in this study (10.8 months) and this compares well with data reported for more recent exploratory combinations such as capecitabine and docetaxel (10.5 months), and epirubicin, docetaxel and cisplatin (11.0 months) (Lee et al, 2004;Park et al, 2004). The same can be said of the progression-free survival period in the ILF group of 4.5 months, which compared well with the 4.1 and 5.2 months reported recently for docetaxel-based regimens (Lee et al, 2004;Park et al, 2004). In other randomised phase II studies, continuous 5-FU/LV infusion plus irinotecan has also provided promising efficacy (ORRs of 40 -42%, median progression-free survival periods of 6.5 -6.9 months and median overall survival periods of 10.7 -11.3 months; Bouche et al, 2004;Pozzo et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…By comparison, there was a nonsignificant trend for increased median survival with ILF in this study (10.8 months) and this compares well with data reported for more recent exploratory combinations such as capecitabine and docetaxel (10.5 months), and epirubicin, docetaxel and cisplatin (11.0 months) (Lee et al, 2004;Park et al, 2004). The same can be said of the progression-free survival period in the ILF group of 4.5 months, which compared well with the 4.1 and 5.2 months reported recently for docetaxel-based regimens (Lee et al, 2004;Park et al, 2004). In other randomised phase II studies, continuous 5-FU/LV infusion plus irinotecan has also provided promising efficacy (ORRs of 40 -42%, median progression-free survival periods of 6.5 -6.9 months and median overall survival periods of 10.7 -11.3 months; Bouche et al, 2004;Pozzo et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…The median overall survival with ELF has been reported at 7.2 and 8.0 months (Vanhoefer et al, 2000;Schulze-Bergkamen et al, 2002), which is similar to both the 8.3 months reported here and the data reported for irinotecanbased regimens in the second-line setting between 7.0 and 7.6 months (Moehler et al, 2003;Assersohn et al, 2004). By comparison, there was a nonsignificant trend for increased median survival with ILF in this study (10.8 months) and this compares well with data reported for more recent exploratory combinations such as capecitabine and docetaxel (10.5 months), and epirubicin, docetaxel and cisplatin (11.0 months) (Lee et al, 2004;Park et al, 2004). The same can be said of the progression-free survival period in the ILF group of 4.5 months, which compared well with the 4.1 and 5.2 months reported recently for docetaxel-based regimens (Lee et al, 2004;Park et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…During the last few years additional drugs were introduced into chemotherapy regimens for gastric cancer such as oxaliplatin, the taxanes and irinotecan. Results from phase II studies indicate a promising efficacy and managable toxicity profile for combination chemotherapies including these new substances (Al-Batran et al, 2004;Bouche et al, 2004;Chao et al, 2004;Lee et al, 2004;Park et al, 2004;Souglakos et al, 2004;Van Cutsem, 2004). One of the remaining challenges is the development of predictive marker profiles to identify patients who will derive both minimal toxicity and maximum benefit from certain chemotherapy.…”
mentioning
confidence: 99%
“…Taxane and cisplatin has been used as a first-line chemotherapy with various schedules and doses since the late 1990s (Roth et al, 2000;Ridwelski et al, 2001;Kornek et al, 2002;Lee et al, 2004). Taxane and cisplatin chemotherapy has produced 30 -50% of RRs as a first-line treatment, but the diseases of responding and nonresponding patients eventually progress (Roth et al, 2000;Ridwelski et al, 2001;Kornek et al, 2002;Lee et al, 2004).…”
mentioning
confidence: 99%
“…Taxane and cisplatin chemotherapy has produced 30 -50% of RRs as a first-line treatment, but the diseases of responding and nonresponding patients eventually progress (Roth et al, 2000;Ridwelski et al, 2001;Kornek et al, 2002;Lee et al, 2004). A randomised phase III trial showed a higher RR (39 vs 23%) and longer time to progression (TTP; 5.2 vs 3.7 months) in DCF (docetaxel, cisplatin, 5-fluorouracil) arm when compared to CF (cisplatin, 5-fluorouracil) arm (Ajani et al, 2003).…”
mentioning
confidence: 99%